Biofortified Orange-Fleshed Sweetpotato Can Meaningfully Reduce the Burden of Vitamin A Deficiency - Lividini, K.; Campos, Hugo; Heck, S.; Birol, E.; Hareau, G. (Elsevier, 2024)
Objectives: Inadequate vitamin A (VA) production and apparent intake are prevalent in Africa and South Asia where the disease burden of vitamin A deficiency (VAD) is concentrated. This study focused on estimating the potential impact of vitamin A-biofortified orange-fleshed sweetpotato (OFSP) on reducing the burden of VAD.